An Optimized, Slowly Digested Savory Cluster Reduced Postprandial Glucose and Insulin Responses in Healthy Human Subjects. Issue 3 (17th January 2019) - Wolever, Thomas M S; Jenkins, Alexandra L; Yang, Jun; Nisbet, Mark; Johnson, Jodee; Chu, YiFang; Pan, Yang
Abstract: Background: Slowly digested carbohydrates are perceived as beneficial by some consumers, and various regulatory bodies have published specific criteria defining lower postprandial glycemic response. We developed an optimized savory cluster snack containing slowly digested starch. Objective: We compared the glucose and insulin responses elicited by the optimized (test-) cluster, a control-cluster, and an available-carbohydrate-matched portion of white bread in healthy individuals. The primary outcome was blood-glucose peak rise. We tested healthy individuals ( n = 25) on 3 occasions using a randomized crossover design. On each occasion, the participants provided fasting blood samples and then consumed 1 serving of test-cluster, control-cluster, or white bread. We then measured the participants' blood-glucose and serum-insulin concentrations over the next 4 h. Results: The test-cluster elicited a significantly lower blood-glucose peak rise (mean ± SEM: 1.24 ± 0.09 mmol/L) and incremental area under the curve (iAUC; 67 ± 8 mmol × min/L) than the control-cluster (2.27 ± 0.13 mmol/L and 117 ± 10 mmol × min/L, respectively) and white bread (2.27 ± 0.16 mmol/L and 114 ± 9 mmol × min/L, respectively). The serum-insulin peak rise and iAUC elicited by the test-cluster (128 ± 13 pmol/L and 6.10 ± 0.73 nmol × min/L, respectively) and white bread (141 ± 20 pmol/L and 6.47 ± 1.11 nmol × min/L, respectively) were significantly lower than those elicited by the control-cluster (205 ± 26 pmol/L and 9.60 ± 1.31 nmol × min/L, respectively). Conclusion: The test-cluster elicited lower glucose and insulin responses than the control-cluster. The results support the hypothesis that the carbohydrates in the test-cluster are digested and absorbed slowly in vivo.